Human Health and Physical Activity During Heat Exposure (SpringerBriefs in Medical Earth Sciences,, 2018)
This book provides fundamental concepts in human thermal physiology and their applications in general public, occupational, military, and athletics settings from the biometeorological perspective. The book includes a section on human physiology, epidemiology and special considerations in aforementioned populations, and behavioral and technological adjustments people may take to combat thermal environmental stress and safeguard their health. The book is the first of its kind to compile multiple disciplines - human physiology, climatology, and medicine - in one to provide fundamental concepts in human thermal physiology and their applications in general public, occupational, military, and athletics settings from the biometeorological perspective; Developed by experts, scientists, and physicians from exercise physiology, climatology, public health, sports medicine, and military medicine; Highlights special considerations and applications of thermal physiology to general public, occupational, military, and athletics settings. .